EFFECT OF ESSENTIAL OIL COMBINATION ON PERFORMANCE, MILK COMPOSITION, BLOOD PARAMETERS AND PREGNANCY RATE IN EARLY LACTATING DAIRY COWS DURING HEAT EXPOSURE - U. Serbester; M. Çınar; A. Ceyhan; H. Erdem; M. Görgülü; H. R. Kutlu; L. Baykal Çelik; Ö. Yücelt; P. W. Cardozo (Journal of Animal and Plant Sciences, 2012)
The objective of this study was to determine effect of an essential oil combination (EOC), which contained cinnamaldehyde and diallyl disulfide on performance, milk composition,  blood parameters and pregnancy rate of early lactating dairy cows during heat exposure. Twenty five Holstein cows (days in milk= 37.4±3.09) were assigned to one of two treatment groups: a Control (n=12) and EOC fed (n=13). Cows were fed a total mixed ration comprising concentrate and silage of common vetch with triticale. The concentrate differed only in the supplementation of EOC at 25 mg/kg concentrate (as fed basis). The experiment lasted 11 weeks. Dry matter intake (DMI) and milk production were measured daily while milk samples were taken twice a week. Blood samples were collected weekly, and ultrasonography was performed at 29 d and 42 d post TAI to determine pregnancy rate. Average of ambient temperature, relative humidity and temperature-humidity index (THI) were 25.9°C, 73.4% and 76.8, respectively. The EOC supplementation had no effect (P> 0.05) on performance, milk composition and pregnancy rate. The EOC, however, increased (P< 0.01) insulin concentration, and tended to decrease (P= 0.074) serum total cholesterol concentration, and increase (P= 0.097) NEFA concentration. In conclusion, EOC supplementation in diets of early lactating dairy cows during heat exposure did not affect milk yield and composition, and pregnancy rate. The increase of insulin and reduction of total cholesterol observed in EOC group needs to be confirmed with further research.
Keywords: Essential oil combination; Cinnamaldehyde; Cholesterol; Diallyl disulfide; Heat stress; Insulin